Erik Eynikel - Tobias Nicklas (ed.), Samson: Hero or Fool? The Many Faces of Samson (Themes in Biblical Narrative 17; Leiden – Boston: Brill 2014) - Rzepka, Barbara (The Biblical Annals, 2016)
Review book: Erik Eynikel - Tobias Nicklas (ed.), Samson: Hero or Fool? The Many Faces of Samson (Themes in Biblical Narrative 17; Leiden – Boston: Brill 2014). Pp. X+244. € 103.00. ISBN 978-90-04-26217-1.